Pengaruh Penerapan Sistem Digitalisasi, Efektivitas Pengendalian Internal, dan Pengungkapan Pengendalian Internal terhadap Nilai Perusahaan - Maria Chiquitita Jasmin; Ayu Puspitasari; Helisa Noviarty (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
Variables that affect company valuation can be seen from the probability level (ROA/Return on Assets), the amount of earnings per share (EPS/Earnings Per Share), and the ratio of liabilities to equity (DER/Debt Equity Ratio). Based on the explanation of the theory and several previous studies, which explain that major changes in the era where digital technology is developing very widely, with the presence of technology creating opportunities in the economic sector that can affect the value of the company. This study aims to confirm that this statement is true that this variable is able to affect the value of the company's infrastructure or not. Processing data from the study used the SPSS version 25 application, with sampling using the purposive sampling method. The number of company samples taken consisted of 22 companies over a 3-year period, namely 2020-2022, and produced 66 samples. The results of this study indicate that the digitalization system, the effectiveness of internal control, and internal control do not have a significant impact on the value of infrastructure partially. The findings of this study state that these variables do not directly affect the value of the company in the context of the sample and time period studied.